Effects of dietary lipid levels on growth performance, whole body composition and fatty acid composition of juvenile gibel carp (Carassius auratus gibelio). (9th September 2014) - Wang, Aimin; Yang, Wenping; Shen, Yonglong; Han, Guangming; Lv, Fu; Yu, Yebing; Huang, Jintian; Zhang, Jiahong
Abstract We evaluated the effects of dietary lipid levels on the growth, whole body composition and fatty acid composition of juvenile gibel carp (Carassius auratus gibelio). Triplicate groups of 120 juvenile Carassius auratus gibelio (average weight: 2.05 g) were fed four isonitrogenic diets formulated with lipid levels of 1.4% (low), 6.1% (control), 11.6% (medium) and 21.1% (high) for 60 days. Weight gain in the 11.6% lipid group was significantly higher than that in the other groups (P < 0.05). The feed conversion ratio decreased and protein efficiency ratio increased (P > 0.05) as dietary lipid levels increased. N‐3 polyunsaturated fatty acids (PUFA) were not detected in faeces. The whole body lipid contents of 11.6% and 21.1% lipid level groups were significantly higher than that of the 1.4% and 6.1% lipid level groups (P < 0.05). The content of whole body n‐3 PUFA in the 21.1% lipid level group enhanced significantly (P < 0.05). The whole body contents of eicosapntemacnioc acid (EPA) and docosahexaenoic acid (DHA) in the 21.1% lipid level group were the highest (P < 0.05). These results indicated that high dietary lipid levels (21.1%) inhibit weight gain and promoted fat and n‐3 PUFA deposition in juvenile Carassius auratus gibelio, which led to liver damage. A dietary lipid level of 11.6% was determined to be optimal for growth performance of juvenile Carassius auratus gibelio.